The Determinants of Transfer Pricing in Energy Sector Companies Listed on the Indonesian Stock Exchange - Kusbandiyah, Ani; Fakhruddin, Iwan; Mudjiyanti, Rina; Priyanto, Eko (Indonesian Journal of Business Analytics, 2024)
This study examines "Determinant Analysis of Transfer Pricing in Energy Sector Companies Listed on the Indonesia Stock Exchange in Energy Sector Companies". The formulation of the problem that will be studied in this research is: Does multinationality, tax haven and yhin capitalization have a positive effect on transfer pricing. And the research objective is to test and find empirical evidence of the effect of multinationality, tax havens, thin capitalization can affect transfer pricing. The sample in this study is the energy sector companies, the data that fits the sample criteria is 38 data. The analytical method used in processing the data uses multiple linear analysis. The results showed that multinationality and thin capitalization had a positive effect on transfer pricing, and tax heaven had no positive effect on transfer pricing. The results of this study are multinationality and thin capitalization have a positive effect on transfer pricing. This result is in accordance with Afifah & Prastiwi (2019) which states that multinational companies have easier access to external funding than domestic companies because funding can be obtained from various sources from the country where the company's affiliation is established.